The Influence of Service Quality, Price and Location on Customer Satisfaction at Bangunan Makmur Cilangkap Store, Jakarta Timur - Yumiati Mawo, Yumiati Mawo; Ahmadun; Nurminingsih; Robert Siregar (Journal of Entrepreneur and Business, 2023)
This study aims to determine the effect of service quality, price and location on customer satisfaction at the Sumber Makmur store, Cilangkap, East Jakarta. The method used in research is a type of quantitative research. The population in this study are customers who are making purchases at the Sumber Makmur Building Store, Cilangkap, East Jakarta. Up to 80 respondents in this study used the incidental sampling technique. The source of data in this research is primary data which is obtained directly through filling out the questionnaires given to the respondents. Data collection techniques using questionnaires or questionnaires. The data analysis method used in this study is structural equation modeling (SEM) analysis and processed using the Smart PLS 3.0 application. Keywords: Service Quality, Price, Location, Customer Satisfaction